1973
DOI: 10.1017/s0021859600057804
|View full text |Cite
|
Sign up to set email alerts
|

The effects of red clover (Trifolium pratense var. redhead), white clover (Trifolium repens var. S 100) or perennial ryegrass (Lolium perenne var. S 23) on the reproductive performance of sheep

Abstract: SummaryDuring 3 years, three groups of 20 Scottish half-bred ewes were grazed on perennial ryegrass, white clover or red clover. During this period the two legumes were oestrogenic, in terms of teat-length extension of wethers, but the perennial ryegrass was not. The white clover was only markedly oestrogenic when there was a high proportion of diseased leaves. The mean litter size and lambing percentage of the ewes grazed on red clover was significantly reduced. White clover, although it was oestrogenic, had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Adams (1979) reported severely depressed incidence of oestrus in clover-affected ewes. In contrast, we found that grazing red clover did not affect the incidence of oestrus over the mating period, a finding supported by Newton & Betts (1973). Barrett et al (1965), using the opposite grazing regime to ours (i.e.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Adams (1979) reported severely depressed incidence of oestrus in clover-affected ewes. In contrast, we found that grazing red clover did not affect the incidence of oestrus over the mating period, a finding supported by Newton & Betts (1973). Barrett et al (1965), using the opposite grazing regime to ours (i.e.…”
Section: Discussionsupporting
confidence: 71%
“…ewes grazed red clover pasture during pregnancy and lactation), did not record any differences in conception to first service, but did note an increase in barrenness. Newton & Betts (1973) noted significant decreases in litter size in the order of 0.5 lambs per ewe during 3 years of grazing. In our experiment, while litter sizes tended to be higher in C ewes during grazing years, differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 92%
“…Histological examination of the cervix revealed that subclinical infertility was widespread in Western Australian flocks [72]. With isoflavone-containing red clover varieties, ewes exposed long-term had a high incidence of abnormalities of the external genitalia, decreased mating performance and fewer multiple births [73,74].…”
Section: Clinical Signsmentioning
confidence: 99%
“…When grazed at or about mating, conception rates and ovulation rates (or lambs born per ewe lambing) are decreased (Morley et al 1964;Newton & Betts 1973;Lightfoot & Wroth 1974). Permanent and progressive infertility occurs when formononetin-rich pastures are grazed for prolonged periods at any time of the year (Barrett et al 1965;Davenport 1967;Davies & Maller 1970).…”
Section: Haymentioning
confidence: 99%